2007
DOI: 10.2353/jmoldx.2007.060170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Markers for CpG Island Methylator Phenotype (CIMP) in Colorectal Cancer by a Large Population-Based Sample

Abstract: The CpG island methylator phenotype (CIMP or CIMP-high) with extensive promoter methylation is a distinct phenotype in colorectal cancer. However, a choice of markers for CIMP has been controversial. A recent extensive investigation has selected five methylation markers (CACNA1G, IGF2, NEUROG1, RUNX3, and SOCS1) as surrogate markers for epigenomic aberrations in tumor. The use of these markers as a CIMP-specific panel needs to be validated by an independent, large dataset. Using MethyLight assays on 920 colore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
416
4
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 311 publications
(442 citation statements)
references
References 32 publications
17
416
4
5
Order By: Relevance
“…Regional 3p22 methylation markers may thus serve as an alternative set of markers to characterize CIMP status, providing further support for the previous recommendation that MLH1 should be included as one of the markers in the panel for the characterization of CIMP þ. 16 It was notable that CIMP þ and the BRAF V600E mutation were all independent predictors of regional 3p22 methylation in multivariate analysis, despite their strong associations with one another. This suggests that heterogeneity in genetic and epigenetic events may still underlie the development of a given subset of colorectal cancers with strong molecular and clinicopathological similarity.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Regional 3p22 methylation markers may thus serve as an alternative set of markers to characterize CIMP status, providing further support for the previous recommendation that MLH1 should be included as one of the markers in the panel for the characterization of CIMP þ. 16 It was notable that CIMP þ and the BRAF V600E mutation were all independent predictors of regional 3p22 methylation in multivariate analysis, despite their strong associations with one another. This suggests that heterogeneity in genetic and epigenetic events may still underlie the development of a given subset of colorectal cancers with strong molecular and clinicopathological similarity.…”
Section: Discussionmentioning
confidence: 92%
“…40 Previous observations between the BRAF V600E mutation and methylation of multiple genes at distinct loci in conjunction with CIMP þ have been reported. 14,16,[47][48] One other study has also reported the close association between long-range epigenetic silencing of the 2q14 region and CIMP þ in sporadic colorectal cancer. 24 Taken together, the independent findings of long-range epigenetic silencing of both the 3p22 and 2q14 regions in the context of CIMP þ provide further support for a common mechanism governing epigenetic dysregulation that presents with the overlapping features of long-range epigenetic silencing and CIMP in the development of sporadic colorectal cancer.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations